Community-Based Integrated Plastic Waste Management: A Case Study in Bali Province, Indonesia - Gede Sedana (Universitas Dwijendra Press, 2026)
Plastics serve important functions in people's daily lives, but they often become waste, polluting the environment and posing a hazard if not managed properly. It's crucial to reduce the use of single-use plastics, recycle recyclable plastics, and choose more environmentally friendly alternatives to mitigate the negative impact on nature and health. This study aims to describe the principles of plastic waste management, the government policy framework, and the role of the government and stakeholders in waste management in Bali. The vast amount of plastic waste in Bali is a serious problem that must be addressed, as the increasing number of residents and visitors or tourists use plastic items in various activities. Plastic waste management is based on five principles: refuse, reduce, reuse, recover, and recycle. Three main pillars are needed in the policy and regulatory framework for plastic waste management in Indonesia, including in Bali Province: a primary legal basis, waste reduction policies, and waste management policies. The increased role of the government and various stakeholders, including universities, the private sector and industry, universities, environmental communities, villagers, and the media, in addressing the plastic waste problem in Bali will support the government in realizing a clean Bali. An integrated strategy is needed to comprehensively address plastic waste, encompassing interventions from upstream (producers) to downstream (processing), and involving three main pillars: policy, infrastructure, and stakeholder behavioural change.